2011
DOI: 10.3354/meps09012
|View full text |Cite
|
Sign up to set email alerts
|

Polychaete species diversity on the West Antarctic Peninsula deep continental shelf

Abstract: We assessed macrofaunal polychaete species diversity on the West Antarctic Peninsula at mean depths of 500 to 600 m along a cross-shelf transect near Anvers Island, Antarctica. Fifteen megacore samples from 3 sites were analysed to species level, revealing 78 polychaete species of which several are new to science. Quantitative samples allowed an assessment of species abundances and the relative contribution of dominance to overall species diversity. The composition of the assemblages varied across the shelf: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Therefore we accept hypothesis 2 and suggest that the proposed increase and subsequent decrease of diversity ( Figure 5) with increasing hydrothermal influence (Bernardino et al, 2012) does not capture the high background biodiversity common in the deep-sea (Rex and Etter, 2010;Chown, 2012; Figure 5). Species accumulation curves from the Bransfield Strait, elsewhere in the Southern Ocean and Pacific SHV (Grassle and Petrecca, 1994;Flach and Heip, 1996;Levin et al, 2009;Neal et al, 2011) show that species richness was higher in background/ inactive sediments than at active vents (Figure 6), which is consistent with lower diversity at active vents (Figure 6). The Bransfield Strait SHV was generally more species rich than vents from the Manus Basin and comparable to NE Pacific vents at Middle Valley (Figure 6; Levin et al, 2009).…”
Section: Controls On Faunal Diversitysupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore we accept hypothesis 2 and suggest that the proposed increase and subsequent decrease of diversity ( Figure 5) with increasing hydrothermal influence (Bernardino et al, 2012) does not capture the high background biodiversity common in the deep-sea (Rex and Etter, 2010;Chown, 2012; Figure 5). Species accumulation curves from the Bransfield Strait, elsewhere in the Southern Ocean and Pacific SHV (Grassle and Petrecca, 1994;Flach and Heip, 1996;Levin et al, 2009;Neal et al, 2011) show that species richness was higher in background/ inactive sediments than at active vents (Figure 6), which is consistent with lower diversity at active vents (Figure 6). The Bransfield Strait SHV was generally more species rich than vents from the Manus Basin and comparable to NE Pacific vents at Middle Valley (Figure 6; Levin et al, 2009).…”
Section: Controls On Faunal Diversitysupporting
confidence: 70%
“…At high temperature vents, meiofaunal taxa showed a similar pattern in species richness to that present here (Gollner et al, 2015), illustrating differences between taxa and environmental settings. Species richness was also generally lower in the Bransfield strait when compared with the West Antarctic shelf seas (Figure 6; Neal et al, 2011) although it should be noted that these samples were from sites ∼500 m shallower and measure only polychaete species richness.…”
Section: Controls On Faunal Diversitymentioning
confidence: 99%
“…For example, using grab samples from Livingstone and Deception Island San Martín et al (2000) recovered 3700 specimens of polychaetes belonging to 89 species. Pabis and Sicinski (2012) collected grab samples at Admiralty Bay, South Shetlands and found 76 polychaete species in depths ranging from 200 to 500 m. Comparative analysis by Neal et al (2011) also showed Admiralty Bay to have a depressed diversity similar to that of species-poor Arctic shelves, although depending on a choice of comparative Arctic site, these results can vary (see Pabis et al 2015c). There are 162 species known polychaete species from Admiralty Bay based on summary of more than 30 years of research in this area (Sicinski et al 2010).…”
Section: Diversity Comparisons Within the Amundsen And Scotia Seasmentioning
confidence: 98%
“…the relative numbers of undescribed species) and stressed that degrees of endemism varied among taxa, but did not make direct global comparisons of Antarctic biodiversity. In global comparisons, Antarctic shelf diversity (of polychaetes) has been shown to be higher than Arctic sites, similar to general bathyal sites and lower than most abyssal sites but comparative data are rare (Neal et al 2011). Gutt et al (2004) estimated that the total expected number of macrozoobenthic species for the entire Southern Ocean shelf lies between 11,000 and 17,000 suggesting Bintermediate^species richness when compared to other selected habitats.…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all previous studies of the Antarctic benthic communities were focused on total polychaete biomass, and there is only scarce knowledge on biomass of particular species (Bromberg et al 2000;Barbosa et al 2010), especially when compared to the abundance data (e.g., Richardson and Hedgpeth 1977;Gambi et al 1997;San Martin et al 2000;Sicinski 2004;Neal et al 2011;Parapar et al 2011). Such data are very important for future assessments of the energy flow in the Antarctic benthic ecosystem.…”
Section: Discussionmentioning
confidence: 99%